Polypropylene-based cork-polymer composites: processing parameters and properties - Fernandes, E. M. (2014)
Cork-polymer composites are one of the most promising fields of cork technology to create materials for a sustainable development. In this work, cork particles and powder were compounded with polypropylene (PP) by twin-screw extrusion and further processed by injection or compression moulding. The obtained PP/Cork injection moulded composites were used to investigate the tensile properties before and after water absorption (WA) tests. The addition of polypropylene-graft-maleic anhydride (PP-g-MA) and stearic acid was evaluated. The composites show good distribution and dispersion of cork with interesting aesthetic characteristics. Low cork content (5wt.%) reinforces the stiffness of the PP. The addition of PP-g-MA up to 8 wt.% promotes an increase on the tensile strength while the stearic acid contributes only with a slight increase on the tensile strain. The thermo-physical properties were investigated and the composites present lowWA. In general the tensile properties of the composites were not significantly affected after theWAtests. Moreover, theWAwas found to increase with an increase in cork content and was reduced with the PP-g-MA and stearic acid. It was also found, that cork act as nucleating agent and promotes antioxidant protection to PP. Both properties ameliorate with the increase of the cork content. Low cork content improves the thermal resistance while increasing the bio-based component increases the composite density and the thermal conductivity. The maximum incorporation of cork on the PP matrix through extrusion process was 93% in volume.